Pyrrolidine ring puckering and prolyl amide bond configurations of 2-methyl-allo-hydroxyproline-based dipeptides. Issue 18 (17th April 2019) - Tiwari, Vinay Shankar; Singh, Gajendra; Gurudayal; Ampapathi, Ravi Sankar; Haq, Wahajul
Abstract : Synthesis and conformational studies of C-2 methylatedd - andl -allo-hydroxyproline containing dipeptides are described. Abstract : An expeditious method for the synthesis of homo and heterochiral dipeptides containingl -alanine andd /l 2-methyl allo-hydroxyl prolines was developed using direct aminolysis of bicyclic lactones derived fromd /l alanine. The impact of C-2 methylation and its spatial orientation on the pyrrolidine ring puckering and prolyl amide bond configuration was ascertained by solution NMR studies. The present studies reveal that C-2 methylation causes the prolyl amide bond to exist exclusively in the trans geometry in both homo- and heterochiral dipeptides. However, the spatial orientation of the C-2 methyl group and its i + 2 position in appropriately capped model dipeptides may nucleate into a turn like structure.